The Iranian nuclear file (the foundations of reality and spaces of ambition) (Journal of the College of Basic Education, 2022)
The early twenty-first century saw an overuse of the theory of the use of force in international relationsEspecially in the Middle East 1, double standards emerged with which the great powers dealWhich contributes to dealing with similar issues in the region, which further complicates the regional situation and accumulatesCrises and their exacerbation Perhaps the most prominent of these issues is the Iranian nuclear file, which has not yet been resolved. And inIn this case, we notice the existence of two conflicting parties, the first represented by the Islamic Republic of Iran, and the secondIn the United States of America. And the parties between them are the units of the international community, such as the European Union and the nationsthe United Nations and others who are trying to intervene as mediators to resolve the issue in a way that satisfies all parties; And theThe US administration insists on accusing Iran of trying to build nuclear weapons.